Resilience Program with University-Community Cooperation for the Prevention of School Dropout: The Case of SOYAC - Münire Kardaş; Özden Bademci; Narin Bağdatlı; Melike Beste Arslan (Anı Publishing, 2022)
Within the scope of school-based community studies coordinated by Maltepe University Homeless and Working Children Application and Research Center (SOYAC), a program aiming at increasing the resilience of students was implemented in a secondary school with high school dropouts. This international program, briefly known as RESCUR, was implemented for one hour two days a week with the cooperation of the interdisciplinary SOYAC team and classroom teachers with a whole school approach. The program aims to protect the right to education of students who are at risk of dropping out of school, to increase their resilience against the disadvantages they experience, to help them gain social and emotional skills, and to strengthen the teachers. In order to understand the experiences of teachers about the application process and their observations and evaluations about their students, the research is designed as a qualitative study through semi-structured interviews. The analysis of the in-depth interviews was carried out using thematic and interpretive phenomenological analysis methods. The themes determined in the research are 'teachers' experiences regarding the RESCUR implementation,' 'the importance of university-community cooperation,' 'the effect of the implementation on the social and emotional development of the students and school culture,' and 'problems encountered in the implementation process.' The results of the research reveal the importance of school-based studies that consider the needs of teachers and students for the elimination of the problems experienced by students at risk of school dropout, the protection of their right to education, and their social inclusion. The implementation is a successful example of the contribution of universities to society in coordinating and cooperating with relevant institutions and organizations in fields such as education, health, and social services for the best interests of the children.